Lake warming intensifies the seasonal pattern of internal nutrient cycling in the eutrophic lake and potential impacts on algal blooms. (1st January 2021) - Yindong, Tong; Xiwen, Xu; Miao, Qi; Jingjing, Sun; Yiyan, Zhang; Wei, Zhang; Mengzhu, Wang; Xuejun, Wang; Yang, Zhang
Highlights: Lake warming has constituted a particular challenge for restoration of eutrophic lakes. Changes of internal loadings are mainly responsible for the seasonal changes of nutrients in the lake. Lake warming would result in more significant seasonal fluctuations in internal loadings. Adaptions in the existing mitigation strategies of eutrophic lake are necessary in a warming world. Abstract: Lake warming induced by climate change has constituted a particular challenge for the restoration of eutrophic lakes. However, a quantitative analysis about impacts of lake warming on the internal nutrient cycling in eutrophic lakes is limited. In this study, monthly nutrient monitoring data set in 2015-2016 in eutrophic Lake Chaohu, China, revealed a regular seasonal pattern of nutrient concentration. A process-based water quality model was established to quantify contributions from internal loadings on seasonal nutrient variations and predict responses under climate change scenarios. Results indicated that internal nutrient loading was responsible for the intra-annual variations of nutrient concentrations in the lake, and the internal loadings fluctuated much more between different seasons than the external nutrient inputs. We predicted that lake warming might probably result in stronger seasonal fluctuations of internal loading and create conditions beneficial for longer duration of cyanobacteria blooms in the year. Evidence derived from this study could help water managers to rethink the existing mitigation strategies in the restoration of eutrophic lakes and emphasize the potential interactions among lake warming, eutrophication and internal nutrient cycling in the future. Graphic abstract: Image, graphical abstract